2011
DOI: 10.3109/10929088.2011.632783
|View full text |Cite
|
Sign up to set email alerts
|

Image guided surgery of the lateral skull base: Testing a new dental splint registration device

Abstract: Objective: The widespread use of image guided surgery in the frontolateral skull base region has been limited by the need for a reliable and non-invasive registration procedure that provides sub-millimetric accuracy. We developed and validated preclinically a non-invasive, easy-to-use registration device based on a dental splint with a laterally mounted fiducial carrier. Methods: Repeated accuracy measurements were performed on six titanium target fiducials which were screwed into the lateral skull base region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The quality of the patient-to-image registration process directly affects the application accuracy of IGNS, and the accuracy of the patient-to-image registration significantly depends on the registration method used. [1][2][3] Patient-to-image registration is achieved by matching corresponding structures in the two spaces, and two types of noninvasive patient-to-image registration methods are currently available in IGNS: point-matching and surfacematching. The first is more widely used in practice.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the patient-to-image registration process directly affects the application accuracy of IGNS, and the accuracy of the patient-to-image registration significantly depends on the registration method used. [1][2][3] Patient-to-image registration is achieved by matching corresponding structures in the two spaces, and two types of noninvasive patient-to-image registration methods are currently available in IGNS: point-matching and surfacematching. The first is more widely used in practice.…”
Section: Introductionmentioning
confidence: 99%
“…An autoregistration device using a malleable adhesive mask with LED markers for the face [24,25] is another noninvasive method that shares a similar theoretical background with the S-STAMP method. Template-based registration using the upper dentition can be applied with minimal invasiveness and serviceable accuracy at the paranasal sinus [26]; however, this registration method did not provide satisfactory accuracy at the lateral skull base [16,27]. The problem lies in the distance from the upper teeth (registration centroid) to the temporal bone, resulting in a larger error [28].…”
Section: Discussionmentioning
confidence: 98%
“…First, we did not average the TREs of different measurement points, as often described in the previous literature [15,16]. This is because we have learned that the TRE is not randomly scattered, but rather a value that is dependent on the distance from the registration centroid.…”
Section: Discussionmentioning
confidence: 99%
“…70% higher TRE (1.59 ± 0.14 mm), and registration of anatomic landmarks resulted in an up to 346% higher mean TRE (4.2 ± 0.73). Ledderose et al [25] observed a mean TRE of 0.33 mm for registration with bone anchored fiducials, whereas surface registration resulted in a higher mean TRE of 1.9 mm. (approx.…”
Section: Addition Of Landmark Registration To Surface Registration DImentioning
confidence: 99%